Some Ecological Issues In a Few Luigi Pirandello's Short Stories - Mihaljevic, Nikica (Richtmann Publishing, 2012)
The research starts from the theory of environmental literary criticism and it uses its methodology in the analysis of some LuigiPirandello's short stories. In a literary text, the ecocriticism analyzes the hierarchical order imposed by the centennial dictatorship ofsome members of the „vertical“ society. This order also inevitably includes some outcast elements which become marginalized by thepolicy of centralism, and the ecocriticism methodology permits the reader to concentrate on these elements. If we try to conceive theconcept of the world not exclusively anthropocentric, it means that a man should interact with the nature, which will lead to the horizontalvision of the society. In this work the focus is on the Pirandello's characters which are described as marginalized, exposed to theatrocities of the social and moral extermination. These characters are assigned the roles of victims, since subject to the discriminatorymechanism. The analysis aims to research whether in Pirandello's literary texts it is possible, by applying the ecocritical methods, toregain the balance among the characters and to equalize all the members of „Pirandello's literary society“.